Loss of Bmal1 impairs the glutamatergic light input to the SCN in mice - Korkmaz, Hüseyin; Anstötz, Max; Wellinghof, Tim; Fazari, Benedetta; Hallenberger, Angelika; Bergmann, Ann Kathrin; Niggetiedt, Elena; Güven, Fatma Delâl; Tundo-Lavalle, Federica; Purath, Fathima Faiba A.; Bochinsky, Kevin; Gremer, Lothar; et al. (Frontiers in Cellular Neuroscience, 2025)
IntroductionGlutamate represents the dominant neurotransmitter that conveys the light information to the brain, including the suprachiasmatic nucleus (SCN), the central pacemaker for the circadian system. The neuronal and astrocytic glutamate transporters are crucial for maintaining efficient glutamatergic signaling. In the SCN, glutamatergic nerve terminals from the retina terminate on vasoactive intestinal polypeptide (VIP) neurons, which are essential for circadian functions. To date, little is known about the role of the core circadian clock gene, Bmal1, in glutamatergic neurotransmission of light signal to various brain regions.MethodsThe aim of this study was to further elucidate the role of Bmal1 in glutamatergic neurotransmission from the retina to the SCN. We therefore examined the spontaneous rhythmic locomotor activity, neuronal and glial glutamate transporters, as well as the ultrastructure of the synapse between the retinal ganglion cells (RGCs) and the SCN in adult male Bmal1−/− mice.ResultsWe found that the deletion of Bmal1 affects the light-mediated behavior in mice, decreases the retinal thickness and affects the vesicular glutamate transporters (vGLUT1, 2) in the retina. Within the SCN, the immunoreaction of vGLUT1, 2, glial glutamate transporters (GLAST) and VIP was decreased while the glutamate concentration was elevated. At the ultrastructure level, the presynaptic terminals were enlarged and the distance between the synaptic vesicles and the synaptic cleft was increased, indicative of a decrease in the readily releasable pool at the excitatory synapses in Bmal1−/−.ConclusionOur data suggests that Bmal1 deletion affects the glutamate transmission in the retina and the SCN and affects the behavioral responses to light.